El Col.lectiu Obertament: una Experiencia de Arte, Creatividad y Terapia en Salud Mental (2000-2010) - GIRAU PELLICER, Teresa; LÓPEZ ANQUELA, Pau; GARCÍA TRIGALES, Luis; BARQUÍN SANMARTÍN, Pilar (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2010)
This article describes a 10-year experience in art therapy with people suffering from severe mental disorders, which is taking place in the region of Gandia (Valencia). What began as a creative workshop and rehabilitation program for a small group of patients residents in a nursing home gave way to the founding of Col.lectiu Obertament which is one of the few Spanish associations made up entirely of people affected by a serious mental illness. Several artistic expressions have been used as a means of social action. The article reports on the ability of art as a mobilizing, integrating and nonstigmatizing element and how this experience has radiated its effects beyond the group who directly participate in it.